Influence of meat attachment factors and food choice motives on the willingness of Filipinos to consume restructured plant-based meat analogues - Jolejole, Sophia Tercelle; Sanchez, Rowena Grace R.; Dognidon, Kenneth Andrew R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2022)
Plant-based meat analogues (PBMA), which are products with characteristics that aim to resemble the experience of consuming meat, has been a topic of interest for several studies due to the benefits they offer to consumers and the environment. To explore how to obtain these benefits, consumer perceptions on PBMA have been studied as consumers are seen as a major factor on the inclusion of PBMA in the diet. This study aimed to determine the validity of existing constructs that were found to influence consumer willingness to consume PBMA in previous research, namely, meat attachment factors and food choice motives (i.e., health and sustainability concerns), as well as how they influence intention to try PBMA. Survey forms were distributed across online platforms and targeted consumers who reside in the National Capital Region. The data collected (n=469) was analyzed through structural equation modelling. Meat attachment factors and food choice motives were found to be reliable predictors of consumer willingness to consume PBMA, however, only three subscales of meat attachment (hedonism, dependence, and affinity) were significantly associated (p<0.0001) with intention to try PBMA. Although meat attachment negatively influences willingness to consume PBMA, hedonism showed opposite results. As a result, PBMA manufacturers and researchers can focus on the mentioned factors in the production of their PBMA products and for future research, respectively. Moreover, the study showed that Filipino consumers were influenced by factors differently compared to other countries. It further validates the need for more local research on PBMA.
Thesis (Bachelor of Science in Food Technology)--University of the Philippines, Diliman
Bibliography : pages 56-67.
Keywords: Meat substitutes -- Philippines; Food preferences -- Philippines